Effectiveness of geosynthetics in stabilizing soft subgrades - Maxwell, Steve; Kim, Woon-Hyung; Benson, Craig H.; Edil, Tuncer (Wisconsin Highway Research Program, 2005)
This report introduced the research begun in 1999 at the University of Wisconsin-Madison to further understand aspects of geosynthetic-reinforced subbases in a pavement system. To learn more about how the performance of highway pavement is improved with geosynthetics, a field demonstration was conducted using a 21-m section along a Wisconsin highway (USH 45) near Antigo, Wisconsin, that incorporated three test sub-sections. Three different geosynthetics including a woven geotextile and two different types of geogrids were evaluated for stabilization. The same pavement structure was used for all test sections except for the geosynthetics. Observations made during and after construction indicate that all sections provided adequate support for the construction equipment and that no distress is evident in any part of the highway. Much has been learned about instrumentation of geosynthetics with foil-type strain gages. The installation procedures and weatherization techniques used during this demonstration project appeared to be a success. Additionally, better strain gage results are possible for a geotextile when a longer (25 mm) strain gage is used. The falling weight deflectometer did not provide sufficient resolution to differentiate between different types of geosynthetic test sections especially in a field environment where there's heterogeneity of natural soils. However, a greater seasonal variability of the subgrade was noted. A control section without reinforcement was not constructed at this time that would have allowed for comparison and assessment of the geosynthetic addition.
88 p.
Keywords: Heterogeneity; Instrumentation; Geosynthetics; Demonstration projects; Geotextiles; Test sections; Weathering; Soils; Subgrade (Pavements); Geogrids; Reinforcement (Engineering); Pavement performance; Soil stabilization; Subbase (Pavements); Strain gages